2019
DOI: 10.1242/jeb.204834
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between suction feeding performance and prey escape response determines feeding success in larval fish

Abstract: The survival of larval marine fishes during early development depends on their ability to feed before depleting their yolk reserves. Most larval fish capture prey by expanding their mouth, generating a 'suction flow' that draws the prey into it. These larvae dwell in a hydrodynamic environment that impedes their ability to capture even non-evasive prey; however, the marine environment is characterized by an abundance of evasive prey, predominantly copepods. Copepods sense the hydrodynamic disturbance created b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Understanding hybrid kinematics, especially in the context of ecological novelty, is informative because: (1) impaired performance in hybrids is a form of extrinsic post-zygotic isolation between species (McGee et al, 2015;Higham et al, 2016) and (2) it can allow the decoupling of morphology, behavior and kinematics, making it easier to identify causative traits underlying performance (Holzman and Hulsey, 2017). Finally, few studies connect observed variation in kinematics to variation in whole organism feeding performance (but see: Svanbäck et al, 2002;Takeuchi et al, 2012;China et al, 2017;Sommerfeld and Holzman, 2019;Whitford et al, 2019). Making this connection is important because it can identify kinematic traits associated with performance tasks relevant to evolutionary fitness rather than simply describing phenotypic variation in kinematic traits, most of which may not be relevant to performance or fitness (Arnold, 1983;Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding hybrid kinematics, especially in the context of ecological novelty, is informative because: (1) impaired performance in hybrids is a form of extrinsic post-zygotic isolation between species (McGee et al, 2015;Higham et al, 2016) and (2) it can allow the decoupling of morphology, behavior and kinematics, making it easier to identify causative traits underlying performance (Holzman and Hulsey, 2017). Finally, few studies connect observed variation in kinematics to variation in whole organism feeding performance (but see: Svanbäck et al, 2002;Takeuchi et al, 2012;China et al, 2017;Sommerfeld and Holzman, 2019;Whitford et al, 2019). Making this connection is important because it can identify kinematic traits associated with performance tasks relevant to evolutionary fitness rather than simply describing phenotypic variation in kinematic traits, most of which may not be relevant to performance or fitness (Arnold, 1983;Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PIV studies on adult fish have indicated a broad variation in peak flow speed for repeated strikes by the same individuals ( Day et al, 2015 ; Holzman et al, 2008 ; Jacobs and Holzman, 2018 ). Such variation was not factored into our modeling, but could contribute to explaining performance differences between similar-sized larvae ( China et al, 2017 ; Sommerfeld and Holzman, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the probability of executing successful prey-acquisition strikes increased with increasing Re ( China et al, 2017 ). Transition into higher Re also improves larval ability to capture highly evasive prey such as copepods ( Jackson and Lenz, 2016 ; Sommerfeld and Holzman, 2019 ; Yaniv et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…where l is length (in m), u is velocity (in m/s) and is kinematic viscosity (in m 2 /s). As is commonly used in the larval fish feeding literature (Krishnan, Nafi, Gurka, & Holzman, 2020;Sommerfeld & Holzman, 2019) and in our previous research on prey capture in guppies (Dial, 2016), we use swimming velocity to calculate Reynolds number.…”
Section: Reynolds Number Manipulationmentioning
confidence: 99%